Humanistic Insights of Korean Nursing Students - Kang, Se-Won (Advances in Social Sciences Research Journal, 2025)
This descriptive research study investigated the humanities insights of Korean nursing students. Participants in this study were 184 nursing students. Data were collected from November 1 to 7, 2024. The humanities insight score of nursing students was 3.34 out of 5 points. History had the highest score in the field of the humanities. Various educational methods should be developed to foster the humanities insights necessary for nursing students to practice the essence of nursing.